Simulation and gaming for mathematical education epistemology and teaching strategies - Piu, Angela 1971-; Fregola, Cesare (Gale Virtual Reference Library, 2011)
This book proposes simulation games supported by the most recent discoveries and advances in theories of learning research, and gears operational decisions toward the development of an integrated system for the teaching of mathematics in primary schools.